2008
DOI: 10.3113/fai.2008.0400
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Compensatory Alignment of the Subtalar Joint to the Progression of Primary Osteoarthritis of the Ankle

Abstract: The varus inclination of the articular surface of the tibial plafond progressed by stages; however, anterior opening was not significant at all stages. The valgus inclination of the subtalar joint progressed until the intermediate stage and converted to varus position at the later stage. CONCLUSION The compensatory function of the subtalar joint was most pronounced at the intermediate ankle arthritis stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 9 publications
3
134
1
Order By: Relevance
“…As reported by Stufkens et al [28], measurement of the medial distal tibial angle depends on radiograph technique and could be different. Our study therefore confirms and quantifies the observations of others who have indicated the common occurrence of coronal plane deformity compensation through the subtalar joint in patients with end-stage ankle arthritis [12,14,21,23]. It adds to the literature how much the coronal plane deformity is for the tibiotalar joint and subtalar joint in patients of end-stage ankle osteoarthritis, thus guiding physicians in achieving optimal positions of these joints.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…As reported by Stufkens et al [28], measurement of the medial distal tibial angle depends on radiograph technique and could be different. Our study therefore confirms and quantifies the observations of others who have indicated the common occurrence of coronal plane deformity compensation through the subtalar joint in patients with end-stage ankle arthritis [12,14,21,23]. It adds to the literature how much the coronal plane deformity is for the tibiotalar joint and subtalar joint in patients of end-stage ankle osteoarthritis, thus guiding physicians in achieving optimal positions of these joints.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is a paucity of published Data presented as mean ± SD; using independent-samples t test; using Mann-Whitney U test; *negative values in talar tilting angle and tibiocalcaneal axis angle indicated varus position; **negative values in moment arm of calcaneus indicated the lowest point of the calcaneus was medial to the bisecting axis line of the tibia. data describing weightbearing ankle and hindfoot alignment in patients with end-stage ankle arthritis [12,21]. We therefore (1) compared ankle and hindfoot alignment of our study cohort with end-stage ankle arthritis with those of a control group; (2) explored the frequency of compensated malalignment between the tibiotalar and subtalar joints in our study cohort; and (3) assessed the intraobserver and interobserver reliability of classification methods of hindfoot alignment used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations